Computational and Experimental Study of the Effect of Operating Parameters on Classification Performance of Compound Hydrocyclone. (29th April 2018) - Jiang, Jin; Ying, Rui; Feng, Jingan; Wang, Weibing
Abstract : Compound hydrocyclone is a kind of dynamic hydrocyclone also with the advantages of static hydrocyclone. In this investigation, the effect of operating parameters on separation performance of compound hydrocyclone is studied using both CFD technique and experimental method. The flow field of compound hydrocyclone was simulated by the RSM turbulence model; the particles with different size were simplified to 6 phases and simulated by the mixture multiphase model. The central composite design method was used to conduct the separation experiment of compound hydrocyclone. The results indicated that compound hydrocyclone can be used for finer particles separation and the flow field of compound hydrocyclone can still achieve a higher centrifugal force in lower inlet velocity. When the minimum partition size is required, the optimized operating condition of the compound hydrocyclone is v = 2.5 m/s, n = 1865 rpm, and c = 7.5%, while when the maximum partition size is required, the optimized operating condition is v = 2.5 m/s, n = 905 rpm, and c = 24.5%.